REVIEW: The Diversity of Indigenous Honey Bee Species of Indonesia - SOESILAWATI HADISOESILO (Society for Indonesian Biodiversity, 2001)
It has been known that Indonesia has the most diverse honey bee species in the world. At least five out of nine species of honey bees are native to Indonesia namely Apis andreniformis, A. dorsata, A. cerana, A. koschevnikovi, and A. nigrocincta. One species, A. florea, although it was claimed to be a species native to Indonesia, it is still debatable whether it is really found in Indonesia or not. The new species, A. nuluensis, which is found in Sabah, Borneo is likely to be found in Kalimantan but it has not confirmed yet. This paper discusses briefly the differencesamong those native honey bees.Â© 2001 Jurusan Biologi FMIPA UNSKeywords: diversity, indigenous, honey bee, Indonesia